Distance Education Possibilities Analysis for Integrated Innovative Projects - Bukhkalo, Svitlana; Byalskiy, Yuri; Aheicheva, Oleksandra; Derkunska, Zhanna (International Journal of Engineering and Technology, 2018)
The materials presented the possibilities development of solar and wind power plants, project development for all those who are engaged in the power studies and baseness. In this, phase of work in NTU "KPI" â€“ studies the possibility of increasing the economic efficiency of alternative energy sources. A review of the literature and the necessary articles written on the subject: Ð°s technologies and economies develop and become more complex, energy needs increase greatly; types and methods of alternative energy, as well as the possibility of calculating the basic set of main economic indicators are classified; identified possible areas of work in obtaining the necessary information and results. Energy is a fundamental input for economic systems. Current economic activity depends overwhelmingly on fossil fuels including oil, coal, and natural gas. These fuels are non-renewable. Renewable sources such as hydroelectric, wind, and solar power currently provide less than 10% of global energy. In just a few decide solar and wind power has developed from alternative energy sources to a new fast growing industrial branch. The history of industrial civilization is a history of energy transitions. In less developed, agrarian economies, people's basic need for food calories is provided through simple forms of agriculture, which is essentially a method of capturing solar energy for human use. As economies develop and become more complex, energy needs increase greatly.Â Â